KETAMINE AS AN OPTIONAL TREATMENT IN CHRONIC PAIN - A REVIEW - Mathias Spitaleri,; Karol Kanon,; Filip Kieloch,; Julia Głowacka,; Agnieszka Fitas,; Wojciech Gąska,; Karolina Dębek-Kalinowska,; Oskar Sienkiel,; Wiktor Gąska,; Dawid Sewruk, (International Journal of Innovative Technologies in Social Science, 2025)
Chronic pain is a pervasive and debilitating condition that affects millions of individuals worldwide. Traditional methods of pain management, including the use of opioids, often fall short in providing adequate relief and come with significant risks, such as dependency and tolerance. As a result, there has been growing interest in exploring alternative treatments, with ketamine emerging as a promising option. Ketamine, a dissociative anesthetic, has shown potential in alleviating various types of chronic pain, including neuropathic pain, cancer-related pain, and pain associated with complex regional pain syndrome (CRPS).Aim of study: This review aims to examine the current evidence on the efficacy of ketamine in chronic pain management, exploring its mechanisms of action, clinical applications, safety profile, and potential limitations.Methods and materials: PubMed and Scopus databases were used to search for topic treated articles.